A Tale of Two Countries: A Story of the French and US Polarization - Julien Albertini; Jean-Olivier Hairault; François Langot; Thepthida Sopraseuth (Institute of Labor Economics (IZA), 2017)
This study investigates job polarization in the United States and in France. In the data, the dynamics of employment shares for abstract, routine, and manual jobs appear very similar in the two countries. This similarity actually hides major differences in the dynamics of employment levels by tasks. In particular, the routine employment level fell significantly in France until the mid-1990s, and then rebounded until 2007. The evolution of US routine employment went in opposite directions to that of the French economy. We then develop a multi-sectorial search and matching model with endogenous occupational choice to disentangle the respective contributions of task-biased technological change (TBTC), labor market institutions (LMI), and rising educational attainment to job polarization. For the US economy, we find that TBTC and the rising supply of skilled labor are the main drivers of polarization in a context of growing employment levels. In France, in contrast, polarization is driven mainly by LMI changes. This led to a sharp drop in routine employment in a context of declining aggregate employment until the mid-1990s, which then reversed when the impact of the minimum wage was alleviated by a subsidy policy targeted at low wage earners. Next, we quantify the welfare consequences of job polarization. Abstract and manual workers are the main winners of job polarization in both countries. Welfare gains and losses are more dispersed in the routine group. The most productive French routine workers would have been worse off without LMI changes. In contrast, displaced low-ability, routine French workers would have preferred a more flexible labor market to improve their employment prospects in their occupational change. All US routine workers suffered as a result of the drop in LMI generosity.
Keywords: E24; J62; J64; O33; 330; search and matching; job polarization; labor market institutions